Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan Pada Claro Hotel Makassar - Sanuar, Tri Reski; Budiyanti, Hety; Kurniawan, Agung Widhi (Politeknik Sawunggalih Aji, 2024)
This research aims to (1) determine whether work motivation partially has a positive effect on employee job satisfaction at Claro Hotel Makassar, (2) determine whether work discipline partially has a positive effect on employee job satisfaction at Claro Hotel Makassar, and (3) determine whether work motivation and work discipline simultaneously have a positive effect on employee job satisfaction at Claro Hotel Makassar. The number of samples used was 120 employees with a quantitative research type. Data collection techniques were carried out by distributing questionnaires. The data analysis technique used was multiple linear regression analysis using the Statistical Product and Service Solution. (SPSS). The research results show that: 1) There is a positive and significant effect of work motivation on employee job satisfaction at Claro Hotel Makassar, 2) There is a positive and significant effect of work discipline on employee job satisfaction at Claro Hotel Makassar, and 3) There is a positive and significant effect of work motivation and work discipline together on employee job satisfaction at Claro Hotel Makassar